A Corpus-Based Analysis of the Descriptive verbs “Describe” and “Illustrate” in BAWE and BASE Corpora - Maghfirah, Adinda; -, Prihantoro (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Descriptive verbs such as describe and illustrate are regularly used in academic English to express meanings, definition, and arguments. Yet their nuanced usage across spoken and written contexts often create challenges for students. This study investigates the grammatical relations and collocational patterns of describe and illustrate in the British Academic Written English (BAWE) and British Academic Spoken English (BASE) corpora and how its function differently in academic contexts. This study utilize Sketch Engines Word Sketch Difference and N-Gram tools, the research systematically analyzes noun and adverb collocates as subjects, objects, and modifiers, as well as multi-word phrase patterns. Results indicate that in BAWE, describe is predominantly associated with concrete noun subjects, whereas illustrate collocates more with abstract nouns in BASE. This research fills a gap by directly contrasting spoken and written academic registers, providing a phrase bank that can help student both in spoken and written text.